ANALYSIS OF HOUSING NEEDS AND DEMAND IN BANDUNG CITY - Indah Apriani, Vina
Housing needs are defined as the number of proper houses needed by new families and families with financial constraints, which determined by summing up the housing needs due to population growth in 2022 and number of housing backlogs in 2017 using descriptive statistical analysis based on secondary data. Housing backlog is the sum of housing shortage and number of uninhabitable houses in the existing year. Housing demand is defined as the amount of savings to buy a house in the form of ownership as a part of investment purpose which is influenced by demographic, social, economic and environmental characteristics obtained by using two-stage estimation analysis, which are, hedonic price of housing and housing demand level formula using multiple linear regression equation. Demographic, social, economic, and housing environment characteristics were obtained through primary data based on questionnaires carried out on several respondents who were heads of family with a multi stage random sampling technique selected from households in Bandung City. This study aims to estimate the needs and level of demand for housing in Bandung City, where the results show that in 2022 the demand for housing in Bandung City is estimated to reach 24,706 units with an average growth rate of housing needs of 13.52% per year. While the results of housing demand level is a function of the estimated housing hedonic price P = 41,779 + 34,532 Number of bedrooms + 7,064 land area - 0,003 density + 3,797 distance to work place - 88,203 inundated dummy and function of estimated housing demand level Ln Q = -2,031 + 1,144 ln total income - 0,019 ln household age + 0,037 ln household size + 0,073 ln length of stay - 0,047 dummy of sex + 0,087 dummy of education - 0,181 dummy of marital status which shows that housing demand level is Rp 288.165 - Rp 534.479 for low cost level, Rp 1.431.965 - Rp 5.276.208 for the middle cost level, and Rp 2.939.476 - Rp 19.860.008 for the high cost level with the total elasticity of family income to housing demand is 1.144.